ANALYSIS OF MATHEMATICAL REPRESENTATION ABILITY ON ASSEMBLAGE MATERIAL FOR JUNIOR HIGH SCHOOL STUDENTS - Anggaraini, Dila; Kartini, Kartini (Jurnal Pendidikan Matematika dan IPA, 2022)
This study aims to provide description of mathematical representation ability of Pekanbaru Junior High School students based on the answers to assemblage questions. The research method Decriptive method in the form of a survey was used in this research. The research subject are 25 students of class VII. The object of research is the ability of students' mathematical representation on the assemblage material. The data analysis technique uses deductive methods by collecting data, processing data, presenting data and also analyzing data with the help of experts and theories from a literature review. Data was collected by measuring written tests about mathematical representation abilities. Consists of 6 assemblage of essay questions with moderate criteria. Through the validity test, valid results were obtained with moderate and high criteria and had moderately correlated reliability with good criteria. The results of the data test and analysis concluded that students' mathematical representation abilities applied to assemblage material had 91% visual representation skills using diagrams, 76% representation skills using mathematical expressions, and 51% mathematical representation skills using words.